Penerapan Odoo sebagai Platform E-Commerce untuk Pengembangan Bisnis Online: Pendekatan Praktis dan Studi Kasus - Sitanggang, Andri Sahata; Fauzi, Muhammad Rafli; Ramadhan, Arif Nur; Juliana, Aditya; Firdaus, Muhammad Haikal (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to explore the use of Odoo as an e-commerce platform in online business development, as well as how companies can increase sales and brand awareness through this platform. Odoo is one of the most popular e-commerce platforms, but many companies still use traditional methods in their business operations. This research uses a qualitative approach with a focus on case studies. Data was collected through a literature study covering e-commerce, Odoo, and online business development, as well as observation of Odoo implementation in the subject business. Thematic analysis was used to identify patterns and key themes, while data triangulation was conducted to ensure the validity of the findings. The results show that Odoo implementation requires several important steps such as installation, configuration of e-commerce modules, site design and development, and feature testing. The key features of Odoo that support online businesses, such as inventory management, order processing, shipment tracking, and payment integration, are proven to improve operational efficiency and customer experience. The impact of Odoo implementation on business performance includes increased productivity, reduced operational costs, and improved customer satisfaction. This research provides practical guidance for companies considering Odoo adoption, as well as a significant contribution to the e-commerce and information technology literature by identifying effective implementation strategies.